Modeling of Electric Field created by Electronic Optical System - Tarvydas, P.; Markevičius, V.; Noreika, A.; Pačėsaitė, E. (Elektronika ir Elektrotechnika, 2005)
Created electronic optical system model is based on finite element method. Libraries of electronic optical system electrodes and presumable electron trajectories were made. Analysis of finite element mesh creation was completed and finite element mesh spacing was determined in the zones of presumable electron trajectories. Tetrahedral mesh was created. Partial electrical field calculations and electrical field calculations with real potential values were performed. Macrocommands for overall electronic optical system construction assembly from separate electrodes and for writing electrode potential and electric field strength values to files were created. These files will be later used in MATLAB program for calculation of electron trajectories in electric field and for solving electron focusing problems. Ill. 9, bibl. 4 (in English; summaries in Lithuanian, English and Russian).